Factors Influencing Charitable Giving in Malaysia: An Islamic Perspective - Mohamad Isa Abd Jalil; Hanudin Amin; Sofri Yahya; Anwar Allah Pitchay; Suddin Lada; Pg Mohd Faezul Fikri Ag Omar (International Centre for Education in Islamic Finance (INCEIF), 2023)
Purpose ― This study aims to discover how Islam, as a religion, influences its believers to contribute in the form of gifts, donations or charity, generally referred to as tabarruʿ. Design/Methodology/Approach ― Structural equation modelling analysis was used to investigate the online questionnaire responses from 402 Muslims who have contributed to charity. Findings ― The study finds that only targhīb (reward) and tarhīb (threat) have a significant positive relationship with tabarruʿ, while iḥsān (excellence) and ukhūwah (brotherhood)―despite showing positive influence―are not significant. It also highlights that the influences of targhīb and tarhīb are more robust when the respondent has a higher level of education. Originality/Value ― To the best of the authors’ knowledge, only a few studies on the influence of religion on charitable behaviour have been carried out. So far, no study has looked at the determining variables from the standpoint of Islam. Research Limitations/Implications ― Due to constraints of time and research funding, the sample population was not drawn from all states in Malaysia. The sample was restricted to Malaysians in Sabah, Malaysia. Practical Implications ― This study highlights that non-profit organisations in Malaysia, especially those from an Islamic background, should be able to organise their fundraising strategies with an emphasis on the factors of targhīb and tarhīb.